2002
DOI: 10.1177/0021955x02038002243
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Stability of LDPE Foams: Modeling and Experiments

Abstract: The thickness change of extruded low density polyethylene (LDPE) foam as a function of the blowing agent and air counter diffusion during the post-extrusion aging process is modeled. The blowing agent and air counter diffusion equations are coupled with the viscoelastic equations to model the foam volume shrinkage and recovery processes in a closed-cell LDPE foam. The variables studied include polymer elastic and viscous constants, foam sheet thickness, cell count and foam density. The mathematical model is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…The shrinking behavior always happened to the soft foams with low modulus or low stiffness. 23 It was mainly related to the displacement of the gas inside cells. Just after foaming, the cells of the TPU foams were supported by CO 2 gas of higher pressure than the ambient pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The shrinking behavior always happened to the soft foams with low modulus or low stiffness. 23 It was mainly related to the displacement of the gas inside cells. Just after foaming, the cells of the TPU foams were supported by CO 2 gas of higher pressure than the ambient pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, these results are in agreement with the variation in strand diameter evidenced in Figure 10. Several papers have already treated this shrinkage issue for lowdensity foams, especially in the case of low density polyethylene foams (31) and PCL blown with CO 2 (32) . Works conducted over the past decade have shown that the contraction of the cellular structure is caused by the buildup of a negative pressure inside the cell cavities.…”
Section: Dimensional Stability Of Low Density Pla Foamsmentioning
confidence: 99%
“…The gas diffusion process in closed cell foams is described for PE foams by Yang, Pilon and Briscoe [24,15,3]. Pilon et al [15] described the effective diffusion coefficient through the foam as a product of the geometric factor and the gas diffusion coefficient through the foam membrane.…”
Section: Aging-dimensional Stabilitymentioning
confidence: 99%
“…8, it is shown schematically that the phenomenon of the so-called breathing foam cells due to diffusion process of blowing agent and molecules of ambient air as described in the literature. Briscoe and Yang [24,3] described the mass diffusion as a function of the blowing agent and the air counter diffusion, but did not take the temperature dependency into account. Fig.…”
Section: Aging-dimensional Stabilitymentioning
confidence: 99%